VSAT Pointing Parameter Calculation Programming with Trigonometry Principles Using NEO6M GPS Module as Coordinate Detection Using C++ Programming Language - Hasanah, Uswatun; Darma Setiawan, Antonius; Jaenul, Ariep (Universitas Muhammadiyah Surakarta, 2024)
Very Small Aperture Terminal or VSAT is a type of telecommunications technology that uses satellites as a transmission medium. In the VSAT installation process there is a process called pointing, which is the process of directing the VSAT vertically and horizontally in the direction of the target satellite. This is very important to do to get good signal quality, so that the service output from the VSAT is good. The position of the VSAT device on earth, while the satellite is in outer space, creates complexity in the pointing process. The parameters to pay attention to when pointing are the azimuth value, namely the direction formed horizontally between the VSAT device and the point 0 degrees north of the earth, as well as the elevation value, namely the angle formed vertically between the VSAT device and the satellite towards the 0 degree point in the horizon plane. To obtain the azimuth and elevation parameters, previous scientists had written them in a mathematical formula with complex trigonometry elements. By using quantitative methods, this journal summarizes the programming of these formulas using the C++ language. This is useful in the future to determine the suitability of calculation results and can be developed further by direct integration into VSAT devices. This research also uses the NEO6M GPS module which can provide coordinate information because it is needed in calculating the formulation. The results of this research are that C++ can be used to program complex trigonometric mathematical calculations and the accuracy of the programmed parameters can be adjusted according to the type of data used. In conclusion, the C++ language can be used to carry out VSAT pointing parameter calculation programs in collaboration with GPS sensor readings with appropriate results.